All roads lead to Rome: QTL analysis for vernalization requirement and dissection of allelic variation uncovered unexpected diversity of FLC loci in Camelina sativa - Roslinsky, Vicky; Chaudhary, Raju; Zatylny, Annette; Parkin, Isobel A. P.; Eynck, Christina (Frontiers in Plant Science, 2025)
Winter camelina (Camelina sativa) is a climate-resilient oilseed crop that has received attention as a feedstock crop for advanced, low-carbon-intensity biofuels. Breeding programs working on winter camelina improvement have to contend with heterogeneous germplasm, oftentimes erroneously identified as winter biotypes, and a gene pool that is much smaller than that of spring-type camelina, the latter having motivated crosses between winter and spring biotypes. For the unequivocal differentiation of winter from spring types at an early stage, breeders require a tool to track the vernalization requirement trait in segregating breeding populations as well as in putative winter cultivars, breeding lines, and accessions to be used as parental lines. Linkage mapping in a winter (‘Joelle’) × spring (‘SES0787LS’) C. sativa biparental F2 population identified two major quantitative trait loci (QTLs) for vernalization requirement on chromosomes 8 and 13. Both regions contained orthologs of Flowering Locus C (FLC), a gene known to have a significant effect on flowering time and vernalization requirement in plants. Based on the FLC gene sequences, allele-specific PCR-based markers were developed, suitable for the routine screening of C. sativa germplasm for the presence of the winter and spring alleles of all three C. sativa FLC orthologs, including a chromosome 20 locus. The analysis of the winter cultivar ‘Joelle’ and a diverse C. sativa germplasm panel uncovered greater than expected variability for the FLC alleles, with most lines possessing several different allele combinations and still undergoing genetic segregation. Contrary to previous reports, spring camelina lines can carry the spring and/or winter alleles of Csa.FLC.C20, indicating that this gene by itself only plays a subordinate role in the regulation of flowering and vernalization requirement. In winter C. sativa germplasm, combinations of Csa.FLC.C08 winter alleles with the winter alleles of one or both of Csa.FLC.C13 and Csa.FLC.C20 result in vernalization requirement, while winter Csa.FLC.C08 by itself leads to a semi-winter type. The results of this study and the tools developed herein are a first step to orchestrating the genes underlying vernalization requirement in C. sativa and developing winter camelina cultivars optimized for different winter environments.